1982
DOI: 10.1007/bf01735933
|View full text |Cite
|
Sign up to set email alerts
|

Desmethyldiazepam kinetics after intravenous, intramuscular, and oral administration of clorazepate dipotassium

Abstract: The pharmacokinetics and bioavailability of desmethyldiazepam (DMDZ), formed from its precursor clorazepate (CZP) dipotassium, were assessed in a series of 17 healthy volunteers aged 21--66 years. After a single 20-mg intravenous dose of CZP, mean kinetic variables for DMDZ were: volume of distribution, 1.24 l/kg; elimination half-life, 65 h; total clearance, 0.24 ml/min/kg. Among males, DMDZ half-life tended to be prolonged and clearance reduced with age, but this was not true for females. After oral administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
2
9
0
1
Order By: Relevance
“…This is consistent with prior reports indicating that withinindividual variations in drug elimination and clearance are far smaller than differ ences observed between individuals [46,[49][50][51]-…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with prior reports indicating that withinindividual variations in drug elimination and clearance are far smaller than differ ences observed between individuals [46,[49][50][51]-…”
Section: Discussionsupporting
confidence: 81%
“…In fact, attending physicians judged that the onset o f sedative effects o f clorazepate dipotas sium after single intravenous doses was slow. We similar ly observed that the onset o f sedation after oral doses of clorazepate in healthy volunteers was far more rapid than after intravenous injection o f the same dose [5], This suggests that in vivo conversion o f clorazepate to desme thyldiazepam is required to cause clinical sedative ef fects, and that this conversion may be relatively slow after intravenous dosage. This slow in vivo conversion is not reflected by low serum desmethyldiazepam concentra tions, inasmuch as clorazepate apparently is converted to desmethyldiazepam in the process o f the analytic measu rement [5,8].…”
Section: Discussionsupporting
confidence: 55%
“…Based on total (free + bound) serum desmethyldiaze- Free clearance, ml/min/kg 6.9 (± 0 .9 ) 2.5 (± 0 . 5 ) pam concentrations, elimination half-life was shorter in patients than in controls, and volume o f distribution was smaller (table 1 ). Total clearance of desmethyldiazepam was similar between groups.…”
Section: Single-dose Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Die Pharmakokinetik von Dikaliumclorazepat wurde von mehreren Arbeitsgmppen untersucht (1,11,15). Auch fur das Benzodiazepin Iäßt sich eine Diskrepanz zwischen den pharmakokmetischen Daten und der klinischen Wirksamkeit feststellen; es gelten aber umgekehrte Vorzeichen: Wahrend die I-IWZ sehr lang ist (im Mittel 65 Stunden), hält die klinisch beobachtbare Wirkung nur einige Stunden an, wobei allerdings angemerkt sei, dai3 die Beurteilung der klinischen Wirkungsdauer eines an~iol~tisch, kaum hypnogen wirkenden Pharmakons naturgernäi3 nicht leichtfällt.…”
Section: Pharmakokinetisch Betrachtet Scheint Einunclassified